2012
DOI: 10.1080/00423114.2012.656658
|View full text |Cite
|
Sign up to set email alerts
|

Modelling and analysis of the crush zone of a typical Australian passenger train

Abstract: In this paper, a three-dimensional nonlinear rigid body model has been developed for the investigation of the crashworthiness of a passenger train using the multibody dynamics approach. This model refers to a typical design of passenger cars and train constructs commonly used in Australia. The highenergy and low-energy crush zones of the cars and the train constructs are assumed and the data are explicitly provided in the paper. The crash scenario is limited to the train colliding on to a fixed barrier symmetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…A typical freight wagon model from GENSYS (Sun et al 2011(Sun et al , 2012 is shown in Figure 1. This model includes 11 masses -one wagon car body, 2 bolsters, 4 sideframes and 4 wheelsets, which are modelled as rigid bodies with six degrees of freedom.…”
Section: Multi-body Rail Wagon Modellingmentioning
confidence: 99%
“…A typical freight wagon model from GENSYS (Sun et al 2011(Sun et al , 2012 is shown in Figure 1. This model includes 11 masses -one wagon car body, 2 bolsters, 4 sideframes and 4 wheelsets, which are modelled as rigid bodies with six degrees of freedom.…”
Section: Multi-body Rail Wagon Modellingmentioning
confidence: 99%
“…At the beginning, a single passenger vehicle was modeled by using GENSYS (Sun et al, 2012(Sun et al, , 2013(Sun et al, , 2017a and its model is shown in Figure 2A. For the better display, one bogie in Figure 2A is zoomed and shown in Figure 2B, which clearly shows the bogie components and connections, and the guard rails on the track are also included.…”
Section: Train-track Multi-body Dynamics Modelingmentioning
confidence: 99%
“…Sun et al. 21 used a multibody dynamics approach to develop a three-dimensional non-linear rigid body model for the investigation of the crashworthiness of a passenger train. Jacobsen et al.…”
Section: Introductionmentioning
confidence: 99%